Stagnansi Perwakafan di Aceh: Analisis Faktor Penyebab - Azharsyah Ibrahim (Media Syari'ah, 2017)
As showed from the data obtained from preliminary research, the condition of waqf endowments in Aceh post tsunami disaster tended to stagnate, especially during the period of 2005 – 2010. Therefore, this article is intended to identify and analyze the determinant factors of the waqf stagnation post disaster in Aceh. Data for this study is gathered through in-depth interviews with 15 respondents consisting of selected waqf officials from the provincial and district offices of Ministry Religious Affairs in Aceh, heads of KUA as waqf managers in some selected districts, the Imam of the selected mosques/meunasahs, and the wakif and/ or their descendants. The findings show that four factors have been identified as the cause of the stagnation. First, the significant increase of land prices. Second, the shift of the Acehnese values to be more materialistic. Third, the fading of social values and brotherhood (ukhwah) among Acehnese. Fourth, there are number of waqf property in Aceh were unproductive.